Avaliação da incapacidade cervical e sua associação com dor miofascial mastigatória e hipersensibilidade mecânica generalizada em indivíduos com disfunção temporomandibular - Costa, Dayse Regina Alves da (2014)
The pain related to temporomandibular disorders (TMD) and cervical disorders have high prevalence in the population and the association between signs and symptoms of TMD and cervical dysfunction is widely explored in the literature. Nevertheless, two systematic reviews have recently been published regarding this topic and both were inconclusive, emphasizing the need for further evidence. Objective: To study the correlation between cervical disability, masticatory myofascial pain and generalized mechanical hypersensitivity in subjects with and without temporomandibular myofascial pain dysfunction. Casuistry and Methods: Two groups composed this controlled cross-sectional study: group I consisted of 27 individuals diagnosed with myofascial pain according to the criteria of the Brazilian version of diagnostic research for TMD (RDC / TMD), and group II consisting of 28 asymptomatic control patients. The clinical variables evaluated were: self-reporting of cervical disability determined using the Neck Disability Index (NDI); pain intensity measured by visual analogue scale (VAS); the pain threshold pressure of the temporomandibular joint, the anterior temporalis, masseter, sternocleidomastoid, upper trapezius and Achilles tendon, measured by a digital algometer. Results: Neck disability was significantly higher in patients with myofascial pain (11.8 ± 7.0) compared with the asymptomatic control group (2.7 ± 2.4). In contrast the PPT was significantly lower in group I when compared to group II, in the different measurement areas, anterior temporalis (2.0 ± 0.8 vs. 2.6 ± 1.1), upper trapezius (2.6 ± 1.2 vs. 3.8 ± 1.8) and Achilles tendon (5.6 ± 1.4 vs. 6.9 ± 2.3). The study verified a negative correlation between neck disability and PPT in all studied structures and a positive correlation between the values of PPT on trigeminal and extra-trigeminal areas (p <0.05).Conclusion: Individuals with TMD masticatory myofascial pain show widespread mechanical hypersensitivity, which is also associated to the report of cervical incapacity.